Icelandic community pharmacists’ expectations of future role extensions and training requirements - A needs assessment - Unnur Karen Guðbjörnsdóttir 1993- (2019)
Introduction: Ever since pharmaceutical companies started producing medicines in large-scale productions the main roles of community pharmacists have been dispensing medicines and consultations to patients. In recent years however, community pharmacists’ roles have been expanding in many countries towards patient-centred care where community pharmacists can provide a range of clinical roles. In Iceland, no known community pharmacists’ role extensions have occurred nor are there any current plans for these extensions. Never before have the expectations of Icelandic community pharmacists towards role extensions been explored, therefore the need for community pharmacists’ role extensions are unknown and the possibility of the pharmacy profession’s development at community pharmacies stays vague. Objective: The aim of this study was to explore and evaluate the need and expectation of Icelandic community pharmacists for future role extensions and assess their training requirements. Methods: This study used a quantitative survey questionnaire methodology and consisted of sending a questionnaire to the participants in an email. A purposive sampling approach was used including all community pharmacist registered with the Icelandic Pharmaceutical Society as well as 4th and 5th year students registered at the Faculty of Pharmaceutical Sciences at the University of Iceland, Reykjavík. After data collection, the data was analysed using SPSS (version 25). Results: 90.2% of all respondents (n=55) saw the need for community pharmacists’ role extensions and every respondent part from one (n=60, 98.4%) was ready to take on additional training to make role extensions in Iceland a possibility. Conclusions: There is a clear need for community pharmacists’ role extensions in Iceland and respondents are over-all positive towards additional training. To implement these role extensions however, additional studies have to be conducted to further explore the possibility of role extensions from more aspects, such as the healthcare system. ...